Modeling physical dimensions of human-environment systems: flood and urban growth in the cities of Kigali, Rwanda and Kampala, Uganda - Pérez-Molina, Eduardo; Sliuzas, Richard; Victor Jetten; van Maarseveen, Martin (AESOP, 2016)
Urban flood problems have been increasing in Sub-Saharan Africa, with a clear social inequity dimension, due to external (e.g. climate change) and internal (urban development pattern) causes (Douglas et al., 2008). While interesting adaptation experiences exist, challenges remain to scale up community level actions to city-wide strategies (Lwasa, 2010), hence this paper’s emphasis on understanding impacts in space and across spatial scales. Further, although significant data gaps persist, both information and knowledge on the growth of Sub-Saharan African cities (e.g. Linard et al., 2013) is creating an opportunity to improve very deficient land use plans and systems (African Planning Association, 2014) with innovative, evidence based policy. Aiming to explore the equity in the distribution of risk due to natural hazards, this paper presents the results of assessing floods caused by land cover change in the cities of Kigali, Rwanda and Kampala, Uganda. Two urban growth models, a spatial statistical model (e.g. Dubovyk et al., 2011) and a cellular automata model (originally developed by Pérez-Molina, 2014), were used to project future land cover scenarios for the cities of Kigali and Kampala, as well as for selected catchments within them; these were then inputted into a runoff-based flood model, openLISEM, for the selected catchments (an example for Kampala, Uganda, is reported in Habonimana, 2014). The results were overlayed with land cover patterns, to assess the impact for different land categories. In particular, we determine (1) if the impact on informal settlement areas is larger than for other urban land use categories and (2) spatial inequality derived from physical processes, by comparing which areas generate runoff and which are most impacted by flooding, and how these differentials interact with land use.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south